Pequenas dramaturgias: imaginar mundos possíveis - Charles Valadares Tomaz de Araújo (2024)
The thesis arises from the unfolding of my trajectory as an artist and researcher of the Performing Arts, in which I intertwined theater, childhood and education. It presents a study carried out based on three fundamental stages: the writing of nine stories, in dialogue with the creative paths of the Italian author Gianni Rodari; sharing these stories, through ten workshops held with nine children linked to the association Casa de Gentil – Culturas e Convívios, located in my hometown (Raposos-MG), in the direction of transforming the material created from the experience of the vivid and writing dramaturgy through children’s eyes. Thus, in this thesis, I briefly share the trajectory of Casa de Gentil, revealing the creative process of new stories and building a phenomenology of the ways of being of the children participating in the research, based on the analysis of the lived experience, having as a compass six existentials (Machado, 2010b): corporeality, linguistics, spatiality, otherness, temporality and worldliness. In the end, I present three small aesthetic dramas created from this analysis and provide guidelines for popular education as Cultural Policy. The thesis, in addition to contributing to thinking about the relationships between dramaturgy and childhood, can encourage artistic-educational processes carried out for and with children.